Determination of saxitoxin in water of Lake Baikal - G. A. Fedorova; A. V. Kuzmin; I. N. Zubkov; I. V. Tikhonova; I. R. Shtykova; T. V. Butina; O. I. Belykh; M. A. Grachev (Acta Biologica Sibirica, 2019)
Samples of surface water were taken in the littoral zone of the Aya and Tutay Bays (the west shore of Lake Baikal), Mukhor Bay (the Maloe More Strait), Posolsky Sor Bay and near Turka village (the east shore of the lake) during the cyanobacterial bloom in summer 2018. Saxitoxin was determined by a procedure based on chemical modification of saxitoxin with 2,4-dinitrophenylhydrazine and the following identification of saxitoxin hydrazone by means of liquid chromatography–mass spectrometry. A modified procedure was proposed for the samples with a low predicted concentration of saxitoxin. It was demonstrated that the concentration of saxitoxin in all the samples was lower than the maximum allowable concentration for drinking water (< 3 μg/L).